The Impact of Private Consumption, Private Investment, and Foreign Capital Inflows on Economic Growth: A Cash Flow Accounting Approach in Indonesia - Arifin, Dinah Tasyanda Nugraha; Sari, Rida Perwita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the influence of private consumption, private investment, and foreign direct investment on the economic growth of Indonesia using the cash flow accounting approach. A quantitative approach was employed, utilizing secondary data from various official sources. The analysis indicates that private consumption significantly affects economic growth, whereas private investment shows no significant influence. However, foreign direct investment has a proven significant positive impact on Indonesia's economic growth. These findings underscore the importance of private consumption and foreign investment in driving national economic growth, while highlighting the need for a better understanding of the factors influencing private investment to enhance its contribution to economic growth.